2000
DOI: 10.1111/j.1528-1157.2000.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Independent Occurrence of the CHRNA4 Ser248Phe Mutation in a Norwegian Family with Nocturnal Frontal Lobe Epilepsy

Abstract: Summary:Purpose: To describe the clinical features of a family from Northern Norway in which autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) is associated with a Ser248Phe amino acid exchange in the second transmembrane domain of the neuronal nicotinic acetylcholine receptor a 4 subunit (CHRNA4). We also tested for evidence of a de novo mutation or founder effect by comparing haplotypes with the original Australian family where the Ser248Phe mutation was first described.Method.\: Clinical details w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Nocturnal frontal lobe epilepsy (NFLE) (Steinlein et al, 1995(Steinlein et al, , 1997(Steinlein et al, , 2000Hirose et al, 1999;De Fusco et al, 2000;Phillips et al, 2001;Bertrand et al, 2005) is one such idiopathic epilepsy syndrome with mutations of genes encoding ion channels. Mutations were identified in genes encoding ␣4, ␤2, and ␣2 subunits of nicotinic acetylcholine (ACh) receptors (nAChRs), CHRNA4, CHRNB2, and CHRNA2, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nocturnal frontal lobe epilepsy (NFLE) (Steinlein et al, 1995(Steinlein et al, , 1997(Steinlein et al, , 2000Hirose et al, 1999;De Fusco et al, 2000;Phillips et al, 2001;Bertrand et al, 2005) is one such idiopathic epilepsy syndrome with mutations of genes encoding ion channels. Mutations were identified in genes encoding ␣4, ␤2, and ␣2 subunits of nicotinic acetylcholine (ACh) receptors (nAChRs), CHRNA4, CHRNB2, and CHRNA2, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that ADNFLE is caused by mutations on a few functionally important sites within the M2. 14 Together with S280F, in vitro expression studies indicate that all CHRNA4 mutations increase receptor sensitivity to acethylcholine, suggesting gain of function. 28,29 In our results, both S280F and S284L showed high phyloP scores and low SIFT scores, indicating that the affected nucleotides are highly conserved and that their amino-acid substitutions will be deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…10 Approximately 10-20% of patients have a positive family history and fewer than 5% a negative one. 11 Among the four mutations in CHRNA4 (Ser280Phe, Ser284Leu, Leu291dup and Thr293Ile), Ser280Phe and Ser284Leu have been identified in several unrelated families (mutation names may be different from those of previous papers; we use NP_000735.1): the Ser280Phe in an Australian, Spanish, Norwegian and Scottish families, [12][13][14][15] and the Ser284Leu in a Japanese, Korean, Polish and Lebanese families. [16][17][18][19] It has been assumed that founder effect is not relevant to ADNFLE, because most of the families studied come from different countries, 20 and a previous haplotype study of the Australian and Norwegian family 14 showed no genetic connection.…”
Section: Introductionmentioning
confidence: 99%
“…Both mutations were shown to have major effects on receptor function in vitro [23][24][25][26]. With the identification of these mutations, subsequently confirmed in families of different origins [27][28][29], ADNFLE became the first epilepsy in which genetic bases were detected, apparently showing features of a monogenic disease. Three de novo or inherited CHRNA4 mutations, occasionally associated with mild-to-moderate mental retardation were later reported [15,[30][31][32][33][34][35][36][37].…”
Section: Genetic Forms Of Nflementioning
confidence: 93%